Impacto del transporte de carga en el ambiente de Ciudad Juárez y revisión de dispositivos de reducción de carga aerodinámica para camiones pesados - Tilvaldyev, Shehret; Caldiño Herrera, Uzziel; Dávalos Ramírez, José Omar; Lira Martínez, Manuel Alejandro (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
Nowadays studying the ways in which greenhouse gas emissions may be reduced from all sectors of human been activities, including the transportation sector, became extremely important. The purpose of this investigation is study environmental impact of freight transportation in cd. Juarez area and review of aerodynamic drag reduction devices for heavy trucks to better understand what technologies or practices can be applied to highway tractor and trailer combinations to reduce aerodynamic drag without negatively affecting the usefulness or profitability of the vehicles.